Oenothera laciniata Hill Extracts Exhibits Antioxidant Effects and Attenuates Melanogenesis in B16-F10 Cells via Downregulating CREB/MITF/Tyrosinase and Upregulating p-ERK and p-JNK - Horng-Huey Ko; Yeo-Tzu Chang; Yueh-Hsiung Kuo; Chia-Hsuan Lin; Yih-Fung Chen (Plants, 2021)
Oenothera laciniata Hill is a perennial herb traditionally used to alleviate inflammatory complications. This study investigated the antioxidant and anti-melanogenic activities of O. laciniata. The methanolic extract (OLM) of O. laciniata and its different fractions, including ethyl acetate (OLEF), n-butanol (OLBF), and water (OLWF) fractions, were prepared. Antioxidant activities were evaluated by total phenolic content, the radical-scavenging effect on 2,2-diphenyl-1-picrylhydrazyl (DPPH•), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS+•), and superoxide anion (O2−•), reducing capacity, and metal chelating ability. OLM and its fractions exhibited potent antioxidant activity in these in vitro assays, with a correlation between radical-scavenging activity and total phenolic content. OLM and its fractions inhibited the mushroom tyrosinase activity superior to the reference control, ascorbic acid. In B16-F10 melanoma cells, OLM and its fractions significantly decreased melanin production and tyrosinase activity. Mechanistic investigations revealed that OLM and its fractions inhibited tyrosinase and TRP-2 expressions via downregulating MITF and phosphorylated CREB and differentially inducing ERK or JNK phosphorylation. Additionally, OLM and its fractions caused no significant cytotoxicity towards B16-F10 or skin fibroblast cells at concentrations used in these cellular assays. These findings demonstrated the potential of O. laciniata extracts as the ideal skin protective agent with dual antioxidant and anti-melanogenic activities.